Explanation and Distinction of the Legal Nature of Permission as a Basis for Permissibility and Permission as a Basis for Agency (Permission as the Source of Permissibility and Permission as the Source of Agency) - Alireza Abbasi; Siamak Jafarzadeh; Seyyed Mahdi Salehi (مطالعات فقه و حقوق اسلامی)
Permission (''Idhn'') is a frequently used concept in the jurisprudential and legal systems of Iran. Identifying and explaining the legal nature of permission is the first step toward analyzing this legal concept, as well as the different areas in which it plays a role. The widespread applications of permission have made it challenging to choose a single nature for it. Scholars who have aimed to identify the legal nature of permission have often focused on its permissive aspect, assigning it a single nature. They then extend this chosen nature to the permission found in ''permissive contracts.'' Accordingly, scholars have argued about whether permissive creation stems from will or legal provision; some consider permission a unilateral legal act (Iqa’), while others see it as a legal event. Viewing permission as a unilateral act or legal event seems accurate only in cases where the granting of permission results in permissiveness. However, in cases where permission becomes a source of representation—or, in other words, when permission leads to the creation of agency, as in contracts of agency—the nature of permission cannot be regarded as a unilateral act. Defining permission as a unilateral act in such cases leads to inconsistencies and fails to align the selected nature with instances where permission forms the basis for agency. Thus, to determine the legal nature of permission, it is necessary to distinguish between the nature of permissive permission and that of permission as a basis for agency (i.e., in permissive contracts) and to examine them separately. According to the authors, the legal nature of permission as a source of permissiveness is unilateral, while permission as a source of agency holds the nature of a contract.